Early ambulation after-grafting of lower extremity burns. Issue 1 (February 2018) - Gawaziuk, J.P.; Peters, B.; Logsetty, S.
Highlights: Early ambulation after skin grafting of a lower extremity (LE) burn is desirable. Compressive dressings minimize shear and permit immobilization of LE skin grafts. Early ambulation is safe and effective after skin grafting of LE burns. Abstract: Objective: Early ambulation of lower extremity burns that undergo a skin graft may help to avoid some of the complications associated with immobilization. Despite recent evidence supporting early ambulation, post-operative immobilization following lower extremity skin grafting is still a common practice. The purpose of this study was to retrospectively assess the outcomes of lower extremity skin graft cases dressed with a multi-layer compression bandage who were ambulated in the immediate post-operative period. Methods: This single centre observational study examined patients with a lower extremity burn that received a compressive dressing (Profore™) application immediately after surgical grafting and were ambulated no later than 1 day post-operatively. Results: Forty-two burn patients (47 limbs) met inclusion criteria for this study. Of these 42 patients, 25 were operated on as an inpatient. The remaining 17 patients were done on an outpatient basis and discharged the same day of surgery. Mean patient age was 48.2 years and 34 (81.0%) of patients were male. Mean TBSA affected was 5.3% (792 cm 2 ). Mean number of procedures was 1 and mean graft take was 98.9%. Nearly all patients were ambulated within 1 day of surgery. The graft take rate across all cases was 98.9 ± 2.3%. No patients failed early ambulation with their compressive dressings, were readmitted or underwent repeated skin grafting. Conclusions: This study demonstrates the excellent graft take rates that can be achieved with immediate ambulation following lower extremity skin grafting and challenges the conventional teaching of post-operative bed rest following lower extremity skin grafting procedures.